Pengaruh Modal Intelektual Terhadap Kinerja Perusahaan Pada Perusahaan Consumer Non-Cyclicals Yang Terdaftar Di Bursa Efek Indonesia Periode 2018 – 2022 - Darniaty, Will Andilla; Aulia, Azkya Rifdah (Jurnal Keuangan dan Perbankan, 2024)
This study aims to examine the influence of intellectual capital and each of its components on the performance of companies in the consumer non-cyclicals sector. Company performance is measured using ROA (Return on Assets), and intellectual capital is measured using VAIC (Value Added Intellectual Coefficient). The study uses company size (SIZE) and leverage (DER) as control variables. The population in this study consists of consumer non-cyclicals companies listed on the Indonesia Stock Exchange for the period 2018 – 2022. The sample selection in this study uses a purposive sampling technique with a total of 61 companies. This study employs a quantitative method, and the data used are annual reports accessed through the Indonesia Stock Exchange and the companies' websites. Data were processed using E-Views 12 with panel data analysis techniques. The results of the study show that intellectual capital (VAIC) has a positive effect on company performance, VACA has a positive effect on company performance, VAHU has a positive effect on company performance, STVA has a positive effect on company performance, SIZE has a positive effect on company performance, and leverage (DER) has a negative effect on company performance.